1999
DOI: 10.1021/jp982921q
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Properties and Potential Energy Surfaces of Electronic States of SbCl2, SbBr2, SbCl2+ and SbBr2+

Abstract: Spectroscopic properties and bending potential energy surfaces of 2B1, 2A1, 2A2, 2A2(2Πg), 4A2(4Πg), and 2B2 electronic states of SbCl2 and SbBr2, and three low-lying electronic states of SbCl2 + and SbBr2 +, (1A1, 3B1, 1B1), have been studied with complete active space self-consistent field (CASSCF) followed by multireference singles and doubles configuration interaction (MRSDCI) methods that included nearly 2 million configurations. The bond dissociation and adiabatic ionization energies of SbCl2, SbBr2, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…We found a theoretical study of SbCl 2 using MRCI in the literature. 28 The MRCI calculations showed that the ground state of SbCl 2 was the 2 B 1 state, as in this work. However, the MRCI significantly overestimated the bond length (2.374 Å) 28 of SbCl 2 compared with that of CCSD(T)/AVQZ (2.333 Å).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…We found a theoretical study of SbCl 2 using MRCI in the literature. 28 The MRCI calculations showed that the ground state of SbCl 2 was the 2 B 1 state, as in this work. However, the MRCI significantly overestimated the bond length (2.374 Å) 28 of SbCl 2 compared with that of CCSD(T)/AVQZ (2.333 Å).…”
Section: Resultssupporting
confidence: 75%
“…However, no experimental results are available for SbX 2 (X = F and Cl) and its anions. We found a theoretical study of SbCl 2 using MRCI in the literature 28 . The MRCI calculations showed that the ground state of SbCl 2 was the 2 B 1 state, as in this work.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation